Respuesta :

Answer:

Equation: y + 1 = -2(x - 0)        OR        y + 3 = -2(x - 1)

Slope: -2

Y-intercept: (0, -1)

Step-by-step explanation:

First, create an equation in point-slope form using ONE point. Using (0,-1):

y - y1 = m(x - x1)

y + 1 = m(x - 0)

Then, use both points to find slope:

[tex]\frac{y2-y1}{x2-x1} =m[/tex]

[tex]\frac{-1-(-3)}{0-1}[/tex]

[tex]\frac{2}{-1}=m=-2[/tex]

Then, plug the slope into the equation and rewrite in the form of y=mx+b:

y + 1 = (-2)(x - 0)

y + 1 = -2x

y = -2x - 1

-1 = b      OR      (0, -1)      

Final answers:

Equation: y + 1 = -2(x - 0)      OR       y + 3 = -2(x - 1)

Slope: -2

Y-intercept: (0, -1)

I hope this helps!